2005
DOI: 10.1097/01.alc.0000175072.17623.f8
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Study of Anxiety Disorder and Alcohol Dependence in Comorbid Alcoholism Treatment Patients

Abstract: Screening for comorbid anxiety disorder in alcoholism treatment patients is warranted and, where found, should be considered a marker of high relapse risk relative to that of noncomorbid patients. The capacity of specific anxiety treatment to mitigate relapse risk among comorbid patients remains an open question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
176
3
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(188 citation statements)
references
References 44 publications
(56 reference statements)
7
176
3
2
Order By: Relevance
“…Identifying consistent predictors of chronic SUDs in prospective studies has been difficult. Some factors suggested in the literature include family history of substance use disorders 8, 9 and Axis I disorders such as major depression 10-15 and anxiety disorders 11, 12, 16, 17 . However, not all studies have had consistent findings on these relationships 5, 17-19 …”
Section: Introductionmentioning
confidence: 99%
“…Identifying consistent predictors of chronic SUDs in prospective studies has been difficult. Some factors suggested in the literature include family history of substance use disorders 8, 9 and Axis I disorders such as major depression 10-15 and anxiety disorders 11, 12, 16, 17 . However, not all studies have had consistent findings on these relationships 5, 17-19 …”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric comorbidity has received considerable attention as a potential predictor of poor treatment outcomes in alcohol-dependent individuals (Bradizza et al, 2006;Kranzler et al, 1996;Krushner et al, 2005). Several studies have found that affective, anxiety, and antisocial personality disorders are associated with a high risk of relapse to heavy drinking (Driessen et al, 2001;Galen et al, 2000;Greenfield et al, 1998;Kranzler et al, 1996;Strowig, 2000;Verheul et al, 1998;Willinger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GABRA2 genotype has been associated with Conduct Disorder problems (Dick et al, 2006,) which have, in turn, also been linked to poor outcome (Myers et al, 1995). Thus, the potential exists for GABRA2 genotype to join the long list of clinical [e.g., severity of dependence (Bottlender and Soyka 2005), comorbid psychopathology (Ciraulo et al, 2003;Kushner et al, 2005;Pettinati et al, 1999)], psychological [e.g., self-efficacy, coping skills (Ciraulo et al, 2003;Maisto et al, 2000)], or biological [e.g., fast β EEG activity, sleep disturbance (Bauer 1994;Bauer 2001;Prichep et al, 1999;Saletu-Zyhlarz et al, 2004;Winterer et al, 1998;Brower et al, 1998;Brower et al, 2001;Clark et al, 1998;Drummond et al, 1998;Gillin et al, 1994)] variables for which a relationship to substance abuse treatment outcome has been demonstrated. If an association with GABRA2 could be demonstrated, then the field may benefit from an expansion of the theoretical framework for interpreting the causes of treatment failure.…”
Section: Introductionmentioning
confidence: 99%